Anestezjologia i intensywna terapiaHigh frequency ventilation for tracheal resection. Description of the six cases - Zajączkowska-Drużba, Katarzyna; Olejnik, Krzysztof; Misiołek, Hanna; Rokicki, Wojciech; Czyżewski, Damian; Filipowski, Marek; Misiołek, Maciej (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2007)
Background: High frequency jet ventilation (HFJV) is an alternative method to conventional ventilation for tracheal resection. Aim: The aim of the study was to analyze usefulness, efficacy and safety of HFJV during tracheal resection. Material and methods: Six patients underwent tracheal resection by use of HFJV. Ventilatory and haemodynamic parameters were measured and recorded. Results: The chosen method of ventilation resulted in haemodynamic and ventilatory stability in all patients during anaesthesia. Conclusion: The results show that HFJV is a safe and effective method of ventilation during tracheal resection.